Determinants of Covid-19 Vaccination Uptake Among the Elderly in Jagakarsa Sub-District, South-Jakarta - Amelia Savitri; Rafiah Maharani Pulungan; Fathinah Ranggauni Hardy; Terry Y.R. Pristya (Universitas Airlangga, 2022)
Background: COVID-19 is considered to be responsible for the emergence of a new dangerous outbreak. Therefore, it is expected that the interest in receiving vaccines will be very high. However, the lowest vaccination uptake rate comes from the elderly population. Objective: To investigate determinants of COVID-19 vaccination uptake among the elderly. Methods: Cross-sectional design study. This research was conducted in Jagakarsa Sub-district from March to July 2021 with an online interview. The sample size was 393 from the total population study of 21,903. The sampling method was purposive sampling with independent variables namely gender, education level, knowledge, attitudes, government policy, health worker’s recommendations, family support, access to COVID-19 vaccination service facilities, perceptions of COVID-19, and perceptions of COVID-19 vaccines. The dependent variable was COVID-19 vaccine uptake. Sample inclusion criteria included the elderly aged ≥ 60 years old and who lived in the Jagakarsa Sub-district. The exclusion criteria were those who were not willing to be respondents. This study conducted a univariate analysis to determine the frequency distribution of variables. Bivariate data analysis that was used were Chi-Square and multivariate data analysis with multiple logistic regression (α=0.05). Results: The results of the bivariate analysis showed that education, knowledge, perceptions of COVID-19 and COVID-19 vaccines, attitudes, government policies, access to COVID-19 vaccination service facilities, health worker’s recommendations, and family support had a significant relationship with COVID-19 vaccine uptake. The results of multivariate analysis showed that the most associated factor was the perception of COVID-19 vaccine with AOR= 9,928 (95% CI: 5,386-18,302). Conclusion: Respondents had a high acceptance of COVID-19 vaccines, whereas most of the respondents were worried about the side effects at the same time. As our findings suggest, informing the elderly about forthcoming vaccines would help to build their trust in the COVID-19 vaccines.